Instruction time and educational outcomes - Andrés Barrios Fernández (IZA World of Labor, 2023)
Increasing instruction time might seem a simple way to improve students' outcomes. However, there is substantial variation in its effects reported in the literature. When focusing on school day extensions, some studies find no effects, while others find that an additional hour of daily instruction significantly improves test scores. A similar pattern arises when examining the effect of additional days of class. These mixed findings likely reflect differences in the quality of instruction or in the activities that are being replaced by additional instruction. Hence these elements need to be considered when designing policies that increase instruction time.
Keywords: I28; I24; I20; 330; instruction time; heterogeneous returns; implementation challenges; education reforms